Do common infections trigger disease-onset or -severity in CTLA-4 insufficiency? - Krausz, Máté; Mitsuiki, Noriko; Falcone, Valeria; Komp, Johanna; Posadas-Cantera, Sara; Lorenz, Hanns-Martin; Litzman, Jiri; Wolff, Daniel; Kanariou, Maria; Heinkele, Anita; Speckmann, Carsten; Häcker, Georg; et al. (Frontiers in immunology, 2022)
Heterozygous mutations in CTLA4 lead to an inborn error of immunity characterized by immune dysregulation and immunodeficiency, known as CTLA-4 insufficiency. Cohort studies on CTLA4 mutation carriers showed a reduced penetrance (around 70%) and variable disease expressivity, suggesting the presence of modifying factors. It is well studied that infections can trigger autoimmunity in humans, especially in combination with a genetic predisposition.
Gesehen am 26.01.2023